Identitas Diri dan Makna Guru Profesional sebagai Komunikator Pendidikan (Perspektif Fenomenologis) - Nur Ainiyah (Jurnal Pendidikan Islam Indonesia, 2016)
In communications education, teaching and learning process is a process of communication that puts the teacher as a communicator or message source education. A communicator of education is required to have professional skills review which is known with academic competence. So the teacher said as a professional teacher if have pedagogic competence, competence personality, social competence and professional competence. Besides the social reality a teacher could must maintain status and role of social by a good attitude and action, teaching profession because in different employees generally. Employees other than teachers, when it had been completed the responsibilities of work in the office can home without Having to act and act like in the office when you're hearts social environment. A teacher with identity he always keeping good temperament in the social environment of the school and environment place he worked. Of course this is a long process in the construction of identity a teacher, teaching experience, time and the decade has passed an externalization process of internalization and its importance on identity that brought. Thus meaning the identity of the teacher to make as a source of Inspiration in school life and social life. And this certainly is correlated with him self as a communicator from the education to make him self not only as a communicator from the education not only as the Source of message but someone (a teacher) that has credibility communicator namely traffic rhetoric, listeners which is good, persuasive, performance keeping, audience analysis, language keeping the body language and use media right so that the process of communication education he becoming the credible communicator.